2009
DOI: 10.1002/jmor.10723
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parity on pelvic size and shape dimorphism in Mus

Abstract: The pelvis is a sexually dimorphic structure and although the causes of that dimorphism have long been studied, relatively little is known regarding the effects of partuitive events on the magnitude of that dimorphism. Here, we use a sample of Mus musculus domesticus to contrast dimorphism in body length and os coxae size and shape between males and parous and nulliparous females. We also test for correlations between relative litter size (L/M) and relative offspring size (O/M) with body length and os coxae si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 55 publications
6
42
0
1
Order By: Relevance
“…Patriquin et al [18] demonstrated that pubic bone and sciatic notch morphology differed between the genders enough to reliably predict gender based on pelvic shape alone. Schutz [19] recently discussed the role of parity on pelvic remodeling. In summary, both congenital and environmental factors may explain variations in correlation noted in this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Patriquin et al [18] demonstrated that pubic bone and sciatic notch morphology differed between the genders enough to reliably predict gender based on pelvic shape alone. Schutz [19] recently discussed the role of parity on pelvic remodeling. In summary, both congenital and environmental factors may explain variations in correlation noted in this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although our data show that female and male trajectories diverge substantially before the attainment of sexual maturity, we further assessed whether maternity (pregnancy and lactation) has an influence on the development of pelvic shape, as reported, for example, in mice (41). To this end, we analyzed pelvic shape variation in a subsample of females with known maternity status.…”
Section: Significancementioning
confidence: 98%
“…We also found that the differences in bone size of the pelvis occur not only between females and males but also between nulliparous and parous females. Parturition may affect the size of various skeletal elements Miller 1999, 2001;Johanson and Berger 2003;Specker and Binkley 2005), but relatively little is known about the effects of parturition event on the pelvis dimorphism in small mammals (Schutz et al 2009b). Our study showed that parous females revealed more profound differences in pubic size from males than nulliparous females.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that pelvic dimorphism may emerge also from functional pressures on the pelvis produced by weight bearing, locomotion, and parturition (Schutz et al 2009b). Weight bearing affects the shape of the pelvis due to the pressures of weight to the rear limb.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation